2021
DOI: 10.3389/fcvm.2021.788655
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lectin-Like Oxidized Low-Density Lipoprotein Receptor-1 With Angiotensin II Type 1 Receptor Impacts Mitochondrial Quality Control, Offering Promise for the Treatment of Vascular Senescence

Abstract: Lectin-like oxidized low-density lipoprotein (ox-LDL) causes vascular senescence and atherosclerosis. It has been reported that ox-LDL scavenger receptor-1 (LOX-1) is associated with the angiotensin II type 1 receptor (AT1R). While mitochondria play a crucial role in the development of vascular senescence and atherosclerosis, they also undergo quality control through mitochondrial dynamics and autophagy. The aim of this study was to investigate (1) whether LOX-1 associates with AT1R, (2) if this regulates mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…Strong inhibition of Drp1 with high dose of mdivi-1 accumulated damaged mitochondria and facilitated cardiac damage by I/R ( 81 ). We also confirmed that high dose of mdivi-1 induced cellular senescence in VSMC treated with ox-LDL ( 151 ). In addition, mitochondrial fusion activator leflunomide used for the treatment rheumatoid arthritis has an adverse effect on humans, resulting in development of pulmonary hypertension ( 178 ).…”
Section: Perspectivesupporting
confidence: 77%
See 2 more Smart Citations
“…Strong inhibition of Drp1 with high dose of mdivi-1 accumulated damaged mitochondria and facilitated cardiac damage by I/R ( 81 ). We also confirmed that high dose of mdivi-1 induced cellular senescence in VSMC treated with ox-LDL ( 151 ). In addition, mitochondrial fusion activator leflunomide used for the treatment rheumatoid arthritis has an adverse effect on humans, resulting in development of pulmonary hypertension ( 178 ).…”
Section: Perspectivesupporting
confidence: 77%
“…Treatment of VSMC with oxidized low-density lipoprotein (ox-LDL) induced mitochondrial fission through activation of phosphorylation of Drp1 at serine 616, and mitophagy derived from LC3-dependent autophagy ( 150 ). Although all autophagy described here so far has been LC3-dependent autophagy, recent studies show that mitophagy derived from LC3-independent and Rab9-dependent autophagy is also related to hyperlipidemia ( 151 ). Hence, the existence of at least two forms of autophagy have been reported.…”
Section: Mitochondrial Dynamics In Cardiovascular Senescencementioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction is closely related to nuclear factor- κ B and oxidized low-density-lipoprotein receptor 1 (OLR1) in atrial tissue during atrial fibrillation [ 90 ]. The association of OLR1 with angiotensin II type 1 receptor (AT1R) plays a crucial role in regulating mitochondrial quality control [ 91 ]. Mitochondrial dysfunction and metabolism are also closely related to hypoxia inducible factor-1 α (HIF1A), mitochondrial dysfunction represses HIF1A protein synthesis, and mitochondrial defect and stabilization of HIF1A act synergistically to activate glycolysis [ 92 , 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…The natural compound resveratrol not only acts as an activator of SIRT1, but also acts as an antioxidant, helping to remove excessive ROS and reducing mitochondrial damage to protect cellular senescence and AAA ( 136 , 137 ). In addition, mdivi1, an inhibitor of Drp1, can also effectively maintain mitochondrial integrity and reduce vascular senescence ( 132 , 138 ). Intervention targets and methods related to MiDAS for the occurrence and progression of AAA are listed in Figure 4 .…”
Section: Evidence and Mechanisms Of Cellular Senescence In Abdominal ...mentioning
confidence: 99%